REPRESENTASI “GHIBAH” DALAM FILM TILIK (SHORT MOVIE 2018) - Eka Aprilia; Muhammad Husni Ritonga; Faisal Riza (Universitas Baturaja, 2022)
This research is entitled “Representation of Ghibah in TILIK Film (Short Movie 2018)”. The purpose of this research is to find out how the representation of Ghibah in the TILIK film (Short Movie 2018). The theory used in this research is Representation Theory. The object of this research is the film TILIK. This research uses a two-stage Roland Barthes semiotic analysis method in which researchers can better understand the meaning of denotation, the connotation obtained in the TILIK film, with visuals as a representation of the dialogue which is the marker in this research. The researcher explained the data analysis with visual as a signifier and audio as a marker then explained the meaning of denotation and connotation. The results of this research describe the social reality that often occurs and is carried out by the community, namely backbiting or gossip other people or Ghibah.